Nutrients removal from raw municipal wastewater using Chlorella vulgaris microalgae - Hadis Mostafaei; Abdolreza Samimi; Soheila Shokrollahzadeh; Salma Karamad; Ali Sheikhinejad (Advances in Environmental Technology, 2023)
This study evaluated the ability of Chlorella vulgaris, a freshwater microalgae species, to remove nutrients from raw municipal wastewater. The wastewater was collected from the initial sedimentation-stage discharge of the treatment plant and used to cultivate the microalgae in both a shaker-incubator and a photobioreactor. The results showed that the microalgae effectively reduced the nitrate, nitrite, phosphate, and ammonium ion concentrations in the wastewater by over 90%. Phosphate removal was particularly efficient in the photobioreactor, with a removal rate of 91%, while the shaker- incubator had a removal rate of 44%. In addition to removing nutrients, the microalgae were also able to significantly reduce the wastewater’s chemical oxygen demand (COD), with a reduction of over 90% from 264 to 23.1 mg/l. The microalgae also had a symbiotic effect on the bacterial colonies present in the wastewater, reducing their numbers by 99% while allowing the microalgae to thrive. The final biomass concentration in the photobioreactor was 2.03 g/l, a higher value compared to similar studies. These results demonstrate the potential of Chlorella vulgaris and other microalgae species for use in wastewater treatment systems.